Sistem informasi manajemen berbasis website menggunakan metode RAD pada komunitas seni Standupindo - Wahyudi, Tri; Andarwati, Mardiana (Journal of Information System and Application Development, 2024)
This research aims to analyze and design a website-based management information system using the Rapid Application Development (RAD) method for the Standupindo Malang Arts Community. Standupindo is a stand-up comedy performing arts community that requires an efficient information system to manage members, events and other related information. The RAD method is used because of its ability to speed up the system development process by involving users in every stage of development. This research includes analyzing user needs in the Standupindo community, as well as designing a system based on the results of this analysis. The resulting information system will allow community members to register, access information about upcoming events, submit stand-up comedy performance material, and interact with other members via the website platform. Thus, this system will increase the efficiency and effectiveness of Standupindo community management. It is hoped that the results of this research will make a positive contribution to the development of the stand-up comedy performing arts community in Malang, as well as become an example for similar communities in implementing a website-based management information system using the RAD method.